Đặc điểm của doanh nghiệp gian lận Báo cáo tài chính, phương thức gian lận và mục đích thực hiện gian lận - Nghiên cứu tại thị trường chứng khoán Việt Nam - Phạm Thị Ngọc, Bích; Mai Đức, Nghĩa; Đinh Ngọc, Tú; Lê Vũ Ngọc, Thanh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
The research aims to identify factors affecting financial statement fraud in three aspects including characteristics of fraudulent companies, methods of fraud schemes, and motivations to commit fraud. The data used includes 3,370 observations from 350 companies listed on the Vietnamese stock exchange from 2013 to 2022. Research results show that companies with high debt ratios or large equity more likely to have committed financial statement fraud. Two common fraud schemes are the overstatement of sales and understatement of expenses, aimed at increasing solvency ratios (e.g., interest coverage ratio), profitability (e.g., earnings per share), and activity (e.g., inventory turnover). More importantly, the study provides evidence of a U-shaped relationship between companies with high debt ratios or large equity and fraudulent financial reporting. Specifically, when the debt or equity ratio is low, companies are less likely commit frauds. However, as the size of equity or debt increases, the likelihood of financial statement fraud also rises.